If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying r + -33 + -2 = 11 Reorder the terms: -33 + -2 + r = 11 Combine like terms: -33 + -2 = -35 -35 + r = 11 Solving -35 + r = 11 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + r = 11 + 35 Combine like terms: -35 + 35 = 0 0 + r = 11 + 35 r = 11 + 35 Combine like terms: 11 + 35 = 46 r = 46 Simplifying r = 46
| 144=-2-6(6)6(10) | | 8t-2=33+t | | 2k+2=-1313k | | 4K=-9k | | 144=-2-6(6+10) | | 130=3x+2y | | 5x+1+4=11+9x | | 3m+2m+4n+3n= | | 9/4x=1/16 | | 2/3x=140 | | 1=12x-8 | | 5x+8=6x-18 | | 10/9c=-81 | | P-3.2=7.6 | | 7.3y-5.8=51.9 | | 53-2x=5x-17 | | 15+9n=9-n | | 2(7x+2)=-12 | | 2/3z=1/21 | | 50=5ln(3x+7) | | 84=2*35+2*w | | X(8-1)=18 | | -1=2x-8 | | -x/4-5=-8 | | -15+t=20 | | 4/3m=8/15 | | a/3-7=10 | | 25x+2000=2000 | | -7(2-6x)-4x=23+x | | -2+3=-(x+6) | | 84+36=93 | | 3*x+sqrt(3)=3*sqrt(3) |